The Expression of the Meaning of "Ugliness" in Different Registers of Language - Qalandarova , Shaxzoda (The Lingua Spectrum, 2025)
This article delves into the multifaceted concept of "ugliness" as expressed through various linguistic registers, including literature, everyday conversations, and social media interactions. By examining these different contexts, the study reveals how the meaning of ugliness is not fixed but varies significantly depending on the speaker, audience, and situation. The exploration highlights the cultural implications of ugliness, showing that the term encompasses not just physical appearance but also deeper emotional and social resonances. Through qualitative analysis, the research aims to enrich our understanding of how language shapes perceptions of beauty and ugliness, ultimately contributing to broader discussions on aesthetics, identity, and cultural values. The findings suggest that language serves as a powerful tool in framing our understanding of these concepts, impacting societal attitudes and individual beliefs about what is considered ugly.